Answer:
x = ± ![\sqrt{7}](https://tex.z-dn.net/?f=%5Csqrt%7B7%7D)
Step-by-step explanation:
Given
x² - 7 = 0 ( add 7 to both sides )
x² = 7 ( take the square root of both sides )
x = ± ![\sqrt{7}](https://tex.z-dn.net/?f=%5Csqrt%7B7%7D)
To substitute, solve for one variable and then plug it into the other equation you have. In this problem, y is already solved for on the top equation (y=x+2), so you just stuff it into the second equation.
y = x + 2
3y = 4x - 2
3(x + 2) = 4x - 2
3x + 6 = 4x - 2
-x = -8
x = 8
y = x + 2 = 8 + 2 = 10
solution:
x = 8
y = 10
hope this helps!! :)